Comprehensive children's mental health services in schools and communities : a public health problem-solving model - Hess, Robyn; Short, Rick Jay.; Hazel, Cynthia (New York : Routledge, 2012)
'In this text, the authors propose a public health model for comprehensive children's mental health services that encompasses, rather than replaces, the traditional model in school psychology'--
Book is accompaniedby one CD/diskette entittle' Comprehensive children's mental health services in schools and communities
Includes bibliographical references (pages 155-178) and index.
Keywords: Child mental health services